2020
DOI: 10.1371/journal.pntd.0008758
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the outbreak signal of COVID-19 before the response of the traditional disease monitoring system

Abstract: New coronavirus cases and related deaths are continuing to occur worldwide. Early identification of the emergence of novel outbreaks of infectious diseases is critical to the generation of timely responses. We performed a comparative study to determine the feasibility of the early detection of the COVID-19 outbreak in China based on influenza surveillance data and the internet-based Baidu search index to evaluate the timelines of the alert signals compared with the traditional case reporting and response syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…We focused on seven key events (events I-VII) within the period from December 31, 2019, when the Wuhan Health Commission announced a possible outbreak of an unknown new pneumonia, to March 18, 2020, one week after the World Health Organization (WHO) declared a pandemic and local pandemic was under control throughout China ( Fig. 2 a) [ 3 , 21 ]. After the Wuhan Health Commission announcement (event I), national-level public attention remained steady at the outset and increased rapidly after two weeks when human-to-human transmission of an unknown new pneumonia was confirmed (event II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on seven key events (events I-VII) within the period from December 31, 2019, when the Wuhan Health Commission announced a possible outbreak of an unknown new pneumonia, to March 18, 2020, one week after the World Health Organization (WHO) declared a pandemic and local pandemic was under control throughout China ( Fig. 2 a) [ 3 , 21 ]. After the Wuhan Health Commission announcement (event I), national-level public attention remained steady at the outset and increased rapidly after two weeks when human-to-human transmission of an unknown new pneumonia was confirmed (event II).…”
Section: Resultsmentioning
confidence: 99%
“…Internet search engine products, such as Google Trends and Baidu Index, have been widely used as indicators to illustrate the collective public attention to COVID-19 [ [18] , [19] , [20] ]. In China, infoveillance studies based on the Baidu Index identified two critical periods for early-stage disease control when national public attention was low [ 9 , 21 ]. In the United States, infoveillance studies using Google Trends showed that the initial public attention to COVID-19 at the national level was limited, short-lived, and even decreased during the critical period when increasingly strong control strategies were put in place [ 13 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the potential to apply analytical models to identify potential outbreaks in response to other diseases [18]. However, these methods rely on large, complex data sets extracted from a specific health system or region [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Outbreak preparedness is the first essential step, and this includes outbreak protocols, designation of coordinators and teams, and the assembly of the necessary materials for outbreak investigation and response, as well as identifying training needs that should be addressed well before the occurrence of an outbreak. A good surveillance system would allow early detection of outbreaks, leading to activities related to outbreak investigation and response [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%